2021
DOI: 10.3345/cep.2021.00108
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and chronic kidney disease: prevalence, mechanism, and management

Abstract: The prevalence of childhood obesity is increasing worldwide at an alarming rate. While obesity is known to increase a variety of cardiovascular and metabolic diseases, it also acts as a risk factor for the development and progression of chronic kidney disease (CKD).During childhood and adolescence, severe obesity is associated with an increased prevalence and incidence of the early stages of kidney disease. Importantly, children born to obese mothers are also at increased risk of developing obesity and CKD lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 97 publications
1
29
0
1
Order By: Relevance
“…Children were eligible if they had obesity (BMI > 95th %ile) and were presenting for a well child visit. We selected young age and obesity as inclusion criteria, as childhood and adolescent obesity has been implicated to increase the risk of later developing CKD [ 30 , 31 , 32 ]. Exclusion criteria included a diagnosis of hypertension, diabetes, or known kidney or heart disease.…”
Section: Methodsmentioning
confidence: 99%
“…Children were eligible if they had obesity (BMI > 95th %ile) and were presenting for a well child visit. We selected young age and obesity as inclusion criteria, as childhood and adolescent obesity has been implicated to increase the risk of later developing CKD [ 30 , 31 , 32 ]. Exclusion criteria included a diagnosis of hypertension, diabetes, or known kidney or heart disease.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the production of inflammatory mediators, such as adipokines and cytokines, and profibrotic factors increase inflammation, endothelial dysfunction, and renal injury. Ultimately, obesity and CKD share a close association; however, the pathophysiology of obesity-related CKD is seemingly multifactorial (19).…”
Section: Effect Of Obesity On Chronic Kidney Disease and Its Progressionmentioning
confidence: 99%
“…Thanks to its endocrine functions, adipose tissue exerts a role in the production of several hormones, cytokines, and chemokines collectively named adipokines. Adipokines are involved in a multitude of processes such as lipid metabolism, insulin resistance, inflammation, atherosclerosis, and extracellular matrix deposition (19). Over and above the widely known mediators TNF-α, IL-6, and MCP-1, the most studied adipokines include leptin and adiponectin.…”
Section: Adipokinesmentioning
confidence: 99%
“…The Moscow Children's hypertension study showed hyperuricemia (>8.0 mg/dL) in only 9.5% of children with normal blood pressure but as many as 49% in children with borderline hypertension and up to 73% of children with moderate or severe hypertension. 7) In a recent issue of Clinical and Experimental Pediatrics, Yim et al 8) reviewed the epidemiology of childhood obesity, the mechanism of obesity in kidney disease, and the management of obesity leading to chronic kidney disease (CKD). The authors emphasized the correlation between maternal obesity and offspring CKD, the effects and mechanisms of obesity on renal dysfunction, and prevention methods.…”
mentioning
confidence: 99%
“…In a recent issue of Clinical and Experimental Pediatrics , Yim and Yoo [ 8 ] reviewed the epidemiology of childhood obesity, the mechanism of obesity in kidney disease, and the management of obesity leading to chronic kidney disease (CKD). The authors emphasized the correlation between maternal obesity and offspring CKD, the effects and mechanisms of obesity on renal dysfunction, and prevention methods.…”
mentioning
confidence: 99%